﻿Prevalence and risk factors of burnout among community pharmacists in Northeast region of Bulgaria - a pilot study - Mariya Ivanova; Anna Todorova; Lora Georgieva (Pensoft Publishers, 2023)
Background: Burnout is described as an emotional, mental and physical exhaustion observed in healthy people and directly related to their professional context. The objective is to study the level of burnout among community pharmacists and to identify the workplace factors affecting it. Materials and methods: Using a questionnaire, specifically designed by the authors of the study, an anonymous survey was conducted in the region of Varna, as the largest region of Northeastern Bulgaria. The questionnaire contains questions about the demographic characteristics; a standardised burnout measure tool (MBI-HSS-MP), and questions regarding the specifics of the work environment. According to MBI-HSS-MP, burnout is associated with high levels of emotional exhaustion (EE) and depersonalisation (DP) and low level of personal accomplishment (PA). Results: The participants in the pilot study were 127 masters of pharmacy. Regarding individual factors, a statistically significant relationship was found between age and the scales emotional exhaustion EE (p = 0.012), depersonalisation DP (0.028) and personal accomplishment PA (p = 0.028). Most susceptible to ЕЕ (p = 0.014) and DP (p = 0.008) were the age group 25-45 years while most satisfied with their PA were in the age group 46-55 years (p = 0.016). From the organisational factors, the large number of patients had the greatest impact on burnout (DP р = 0.000 /ЕЕ р = 0.006). The other key factors for burnout were an insufficient number of pharmacy staff, a heavy administrative burden and a wide range of medicinal products. Conclusion: It is necessary to develop training courses for young professionals to introduce them gradually into the work process and build up skills for effectively coping with stress. Proposals need to be made for reducing the administrative burden of pharmacists and maintaining staffing levels that are adequate to the patient flow and expanding the capabilities of The Specialised Electronic System for Tracing and Analysis System of Medicinal Products (SETASMP).